Endowing future harvests: the long-term costs of conserving genetic resources at the CGIAR Centres: A report prepared for the CGIAR System-wide Gentic Resources Programme by the International Food Policy Research Institute (IFPRI) in collaboration with the University of California, Berkeley - Koo, B.; Pardey, Philip G.; Wright, B.D.; CGIAR Systemwide Genetic Resources Programme; International Plant Genetic Resources Institute (2002)
At present the CG genebanks, like the CG generally, are financed from short-term (often year-by-year) pledges of support to the system and its centres by its members and from project funds with limited lives (sometimes five years, but often three or less). Germplasm conservation is a very long-term, if not in perpetuity, proposition, and so the mismatch between the short-term nature of the financial support and the long-term nature and intent of the effort is a serious concern. This paper describes our best estimates of the annual funds required to support the core conservation and distribution services provided by the CG genebanks, and uses these cost estimates to determine the size of endowment fund required to underwrite these core conservation services in perpetuity, along with the distribution efforts that ensure this material remains available on demand to breeders, scientists and others worldwide.